Existence and multiplicity of solutions to a class of elliptic problems involving operators with variable exponent - Juárez Hurtado, Elard (2016)
We study the existence and multiplicity of nontrivial solutions for two classes of elliptic problems. The first problem covers a general class of operators with variables exponents where the nonlinearitv has subcritical growth. The second problem is a nonlocal elliptic problem where the nonlinearitv has critical growth. ... continua